Porous lead-free piezoelectric ceramic element, air-coupled porous lead-free ultrasonic transducer and preparation method thereof
Porous lead-free piezoelectric ceramic components are prepared through 3D printing, and the porosity and pore structure are adjusted, which solves the problems of high acoustic impedance and low sensitivity of traditional ultrasonic transducers, and achieves higher sensitivity and environmentally friendly lead-free materials applications.
Patent Information
- Application Number
- CN202310170537.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The acoustic impedance of traditional piezoelectric air-coupled ultrasonic transducers is high, resulting in low ultrasonic energy transmission efficiency, limiting their sensitivity and application scenarios. At the same time, traditional PZT materials contain lead and have a great environmental pollution.
Porous lead-free piezoelectric ceramic components are prepared by 3D printing technology. By adjusting the porosity and pore structure, the acoustic impedance is reduced and the acoustic impedance matched with the air, thereby improving the sensitivity of the ultrasonic transducer.
The acoustic impedance is reduced, the sensitivity of the ultrasonic transducer is improved, and the detection sensitivity reaches below -27dB, which can better detect small signal defects in the material, and lead-free material reduces environmental pollution.
Smart Images

Figure CN116813334B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultrasonic transducers, and in particular to a porous lead-free piezoelectric ceramic element, an air-coupled porous lead-free ultrasonic transducer and a preparation method thereof. Background Art
[0002] Piezoelectric air-coupled ultrasonic transducers have the advantages of being completely non-invasive and non-contact and are widely used in the field of non-destructive testing (such as food, medical treatment, new energy, etc.). Traditional piezoelectric air-coupled ultrasonic transducers are composed of piezoelectric elements, matching layers, backings, shielding interfaces, signal lines, and shells (some probes also have matching circuits). As the core element for realizing the mutual conversion of electrical signals and ultrasonic signals, piezoelectric elements are mostly prepared into 1-3 composite piezoelectric elements (1 represents one-dimensional interconnection of piezoelectric ceramics, and 3 represents three-dimensional interconnection of resins), and ceramic sheets are cut into ceramic column arrays, and epoxy resin is poured into the gaps of the arrays, and the excess resin is ground off after the resin is cured. The 1-3 composite piezoelectric element can effectively reduce the acoustic impedance of piezoelectric ceramics, which is conducive to the acoustic impedance matching of piezoelectric elements and air. However, due to the high volume fraction of ceramics in the 1-3 composite piezoelectric element of the air-coupled ultrasonic transducer, its acoustic impedance is still high, reaching 5 to 30 MRayl, resulting in only a small part of the ultrasonic wave being able to enter the piezoelectric element from the air and be received, limiting the sensitivity of the air-coupled ultrasonic transducer.
[0003] At present, the sensitivity of the piezoelectric air-coupled ultrasonic transducer (used for analysis of composite materials and metal flaw detection) on the market with an operating frequency of 200 to 500kHz is -30 to -40dB (test distance 10cm). This is a big gap compared to the sensitivity of the hydroacoustic transducer, which is -10 to -20dB (test distance 50cm). Therefore, it is difficult for the air-coupled ultrasonic transducer to respond to the small signals generated by some material defects (defects deeper inside the material), which limits its use scenarios.
[0004] The piezoelectric ceramics used in traditional transducers are mostly PZT materials, which contain lead, which can pollute the environment and increase the cost of disposal after scrapping. Summary of the invention
[0005] In view of the problems in the prior art, the purpose of the present invention is to provide a porous piezoelectric ceramic element, an air-coupled porous lead-free ultrasonic transducer and a preparation method thereof. The element is prepared from lead-free ceramics as raw materials to eliminate environmental pollution and facilitate subsequent recycling and treatment. And lead-free ceramics need to have good piezoelectric properties so that the transducer can better realize the conversion of electrical energy and acoustic energy and improve the performance of the transducer. The present invention adopts 3D printing (DLP) to prepare porous piezoelectric elements to achieve adjustable porosity of piezoelectric elements, and adjusts the acoustic impedance of piezoelectric elements by adjusting the porosity, thereby reducing the difficulty of matching the acoustic impedance of piezoelectric elements with air, and improving the sensitivity of the transducer to receive signals.
[0006] The technical solution of the present invention is as follows:
[0007] A porous lead-free piezoelectric ceramic element, wherein the pores in the element are evenly distributed, the porosity is 55%-75%, and the pore structure is Gyroid; the preparation method thereof comprises: the lead-free ceramic powder is 3D-printed into the porous piezoelectric ceramic element by photocuring.
[0008] In a more preferred technical solution, the pores are in various shapes such as spherical and diamond shapes, and combined with the pore distribution and pore structure, they have good strength, high piezoelectricity, and low acoustic impedance.
[0009] In a preferred technical solution, the chemical formula of the lead-free ceramic powder is 0.51Ba(Zr 0.2 Ti 0.8 )O3-0.49(Ba 0.7 Ca 0.3 )TiO3.
[0010] In a more preferred technical solution, the 3D printing further includes: using a Matlab plug-in to design the aperture size, hole shape and porosity according to actual use requirements.
[0011] The method for preparing the porous lead-free piezoelectric ceramic element comprises the following steps:
[0012] S1. Preparation of lead-free ceramic powder
[0013] According to the chemical formula 0.51Ba(Zr 0.2 Ti0.8)O3-0.49(Ba 0.7 Ca 0.3 )TiO3, BaTiO3, TiO2, CaCO3, ZrO2 powders are placed in a ball mill, and anhydrous ethanol is poured into the powder; the ball mill is placed in a ball mill, and ball milled at a speed of 260r / min for 10 to 14h; the powder is obtained after drying; the powder is placed in a crucible and pre-fired in a muffle furnace, and during pre-fired, the temperature is raised to 1220 to 1250°C at a heating rate of 4 to 5°C / min and kept warm for 3 to 5h; the pre-fired ceramic powder is placed in a ball mill and anhydrous ethanol is added, and ball milled at a speed of 260r / min for 20 to 30h; the ball mill slurry is dried for 12 to 14h to obtain ceramic powder, and the ceramic powder is passed through a 60 to 100 mesh sieve to obtain a fine and uniform ceramic powder required for 3D printing;
[0014] S2.3D printing porous lead-free piezoelectric ceramic components
[0015] The ceramic powder obtained by S1 was made into printing slurry, and the slurry was poured into the DLP printer. The required void structure and void ratio were designed using the Matlab plug-in. 2Print layer by layer at a power of 15s; debind the printed parts, use a tubular furnace for vacuum debinding, heat up to 200℃ at 0.2℃ / min, keep warm for 2h, heat up to 400℃ at 0.3℃ / min, keep warm for 3h; heat the debinded prints in a muffle furnace at 5℃ / min to 1500℃ and keep warm for 4h.
[0016] In a preferred technical solution, in step S2, the ceramic powder obtained in S1 is made into a printing slurry, which specifically includes the following steps:
[0017] Weigh the ceramic powder prepared by S1 and pour it into a ball mill, add a dispersant and a surfactant with a mass of 1% of the mass of the ceramic powder, add anhydrous ethanol and zirconium oxide balls, grind the mixture at a speed of 300rpm for 12 hours, place it in an oven for 10 hours after ball milling, fully remove the anhydrous ethanol, grind it in a mortar, and pass it through a 200-mesh fine sieve to finally obtain a ceramic fine powder with uniform particle size distribution and surface modification; according to the solid content requirement of the piezoelectric ceramic slurry (volume fraction of 42% to 49%), weigh the corresponding mass of the modified ceramic fine powder, and weigh a Triton X-100 dispersant with a mass of 0.5%-2% of the mass of the piezoelectric ceramic powder; according to the requirements of the photocuring activity and viscosity of the piezoelectric ceramic slurry, select a suitable acrylate monomer (such as: HEA, HDDA, TMPTA, etc., as the functionality of the acrylate monomer gradually increases, the viscosity of the 3D printing slurry also increases), and weigh 1%-3% of the monomer mass TPO photoinitiator, and finally weigh 0.5% to 0.6% of the non-silicon defoaming agent accounting for the total mass of the piezoelectric ceramic slurry; all the above ingredients are mixed by ultrasonic vibration for 30 to 40 minutes and put into a ball mill; ball milling is carried out at a speed of 250 rpm for 3 to 4 hours, and the obtained slurry is then subjected to vacuum degassing treatment to finally obtain a piezoelectric ceramic slurry with low viscosity, high solid content, high photocuring activity and uniform dispersion.
[0018] The air-coupled porous lead-free ultrasonic transducer comprises the porous piezoelectric ceramic element.
[0019] The method for preparing the above-mentioned air-coupled porous lead-free ultrasonic transducer comprises the following steps:
[0020] S3. Fabrication of air-coupled porous ultrasonic transducer
[0021] Epoxy resin, curing agent and hollow glass microspheres are mixed in a mass ratio of 5:1:5-6, and cured at 80°C for 8-12 hours to obtain a matching layer, and the cured matching layer is polished to 2 mm; the porous piezoelectric element is connected with a wire to bond the matching layer to the porous piezoelectric ceramic element to obtain an air-coupled porous transducer.
[0022] The air-coupled porous transducer provided by the invention directly uses air as a backing and has high sensitivity.
[0023] It should be noted that the epoxy resin and curing agent described in the present invention are common combinations that can be selected by those skilled in the art. In the embodiments of the present invention, e51 epoxy resin and t31 curing agent are used as examples.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The porous lead-free piezoelectric ceramic element provided by the present invention reduces the acoustic impedance to 5.95 MRayl through the design of pores, which is conducive to achieving acoustic impedance with air and increasing the energy of ultrasonic waves received in the air.
[0026] The air-coupled porous lead-free ultrasonic transducer provided by the present invention has a detection sensitivity of less than -27 dB, which is conducive to the detection of small signal defects generated in the material part. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a graph of the piezoelectric constant test results of piezoelectric ceramics.
[0028] Figure 2 is the relationship between porosity and piezoelectric constant.
[0029] Figure 3 is the relationship between porosity and piezoelectric voltage coefficient.
[0030] Figure 4 It is the relationship between porosity and acoustic impedance.
[0031] Figure 5 These are the actual pictures of the prepared lead-free porous piezoelectric ceramic element (a) and the air-coupled porous lead-free ultrasonic transducer (b).
[0032] Figure 6 This is the performance test result of the air-coupled porous lead-free ultrasonic transducer in Example 6.
[0033] Figure 7 This is the performance test result of the air-coupled porous lead-free ultrasonic transducer in Example 1. DETAILED DESCRIPTION
[0034] Examples 1-5
[0035] The porous lead-free ceramic component has a porosity of 55%, 60%, 65%, 70%, and 75% in sequence, a gyroid pore structure, and a diamond pore shape. The preparation method thereof comprises the following steps:
[0036] Step 1: Preparation of lead-free ceramic powder
[0037] This step is to prepare the ceramic powder required for the subsequent photocuring 3D printing of porous piezoelectric elements. 0.2 Ti 0.8 )O3-0.49(Ba 0.7 Ca 0.3 )TiO3 (has good piezoelectric properties, is non-toxic and environmentally friendly) chemical formula, weigh BaTiO3, TiO2, CaCO3, and ZrO2 in molar ratio. Put the prepared powder into a ball mill and pour anhydrous ethanol to submerge the powder. Put the ball mill into a ball mill and mill it at a speed of 260r / min for 12h. After ball milling, pour the slurry into a tray and dry it for 12h to obtain ceramic powder. Put the powder into a crucible and pre-burn it in a muffle furnace. During pre-burning, heat it to 1230℃ at a heating rate of 4℃ / min and keep it warm for 5h. Put the pre-burned ceramic powder into a ball mill and add anhydrous ethanol, and mill it at a speed of 260r / min for 24h. After drying the ball mill slurry for 12h, ceramic powder is obtained. The ceramic powder is sieved through a 60-mesh sieve to obtain a ceramic powder with fine and uniform particle size required for 3D printing.
[0038] In order to test the performance of ceramic powders, the ceramic powders prepared in the above Examples 1-5 were granulated with PVA and dry-pressed into Φ10x0.5 mm ceramic sheets (pressure 80-100 MPa, holding time 30-60 s). Sintering was performed in a muffle furnace with a heating rate of 2.5°C / min to 650°C. The temperature was kept for 30 minutes to remove the PVA. After the binder was removed, the temperature was increased from 650°C to 1500°C at a rate of 5°C / min and kept for 4 hours. The sintered ceramic sheets were coated with low-temperature silver paste as electrodes (dried at 90°C). The ceramic sheets were polarized at room temperature for 10 minutes at a voltage of 3 kV / mm. The piezoelectric properties of the ceramic sheets were tested using a quasi-static d33 tester. Figure 2 shown.
[0039] from Figure 2 It can be seen that the piezoelectric performance of the prepared lead-free ceramic is about 405pC / N, while the piezoelectric performance of PZT-5 piezoelectric ceramics sold on the market is about 420~480pC / N, which is a big difference.
[0040] Step 2: Printing of porous piezoelectric elements
[0041] This step is divided into the preparation of printing slurry and the printing of the required porous structure piezoelectric elements, as well as the sintering of ceramics. Configuration of printing slurry: weigh a certain mass of homemade piezoelectric ceramic powder and pour it into a ball mill, add a dispersant and surfactant with a mass of 1% of the mass of the piezoelectric ceramic fine powder, add anhydrous ethanol and zirconium oxide balls, grind the mixture at a speed of 300rpm for 12 hours, place it in an oven for 10 hours after ball milling, fully remove the anhydrous ethanol, grind it in a mortar, pass through a 200-mesh fine sieve, and finally obtain a piezoelectric ceramic fine powder with uniform particle size distribution and surface modification. According to the solid content requirements of the piezoelectric ceramic slurry, weigh the corresponding mass of the modified piezoelectric ceramic powder, and weigh the Triton X-100 dispersant with a mass of 0.5%-2% of the mass of the piezoelectric ceramic powder. According to the requirements of the photocuring activity and viscosity of the piezoelectric ceramic slurry, select a suitable acrylic monomer, weigh a TPO photoinitiator with a mass of 1%-3% of the monomer mass, and finally weigh a non-silicon defoamer accounting for 0.5% of the total mass of the piezoelectric ceramic slurry. All the above ingredients were mixed by ultrasonic vibration for 30 minutes and placed in a ball mill. Ball milling was performed at a speed of 250 rpm for 3 hours. The obtained slurry was then vacuum degassed to finally obtain a piezoelectric ceramic slurry with low viscosity, high solid content, high photocuring activity, and uniform dispersion. For 3D printing of porous ceramics, the required void structure and void ratio were first designed using the Matlab plug-in. The slurry was poured into the DLP printer and printed at a power of 10 mW / cm 2 Print layer by layer at 15s of light power. Debind the printed parts, use a tube furnace for vacuum debinding, heat up to 200℃ at 0.2℃ / min, keep warm for 2h, heat up to 400℃ at 0.3℃ / min, keep warm for 3h. Heat the debinded parts in a muffle furnace at 5℃ / min to 1500℃ and keep warm for 4h.
[0042] The sintered printed part was coated with medium-temperature silver paste as an electrode (heating at 5℃ / min to 500℃ for 1h). The printed part was polarized at room temperature for 10min at a voltage of 3kV / mm. Its piezoelectric constant was tested. The results are as follows Figure 3 As shown in Figure 2, the piezoelectric constant of the piezoelectric element remains basically unchanged as the porosity increases. 33 Use ZJ-3AN quasi-static d 33 Tester to perform the test.
[0043] The dielectric constant of ceramics with different porosities was tested using a digital bridge, and the piezoelectric voltage constant g of ceramics with different porosities was calculated. 33 , the calculation formula is shown in the figure, and the result is Figure 4 As shown in Figure 2, the piezoelectric voltage constant g increases with the porosity of the piezoelectric ceramic. 33 A high piezoelectric voltage is beneficial to improving the sensitivity of the ultrasonic transducer as a receiving probe.
[0044]
[0045]
[0046] where ε r is the relative dielectric constant, ε is the sample dielectric constant, ε0=8.85x10 -12 F / m is the dielectric constant of air.
[0047] The acoustic impedance is calculated by the following formula:
[0048] Z=ρc(4)
[0049] c=2f p t (5)
[0050] Where Z is the acoustic impedance, c is the sample sound velocity, ρ is the sample density, and f p is the anti-resonance frequency (measured by a digital bridge), and t is the sample thickness.
[0051] like Figure 5 As shown, as the porosity of the porous piezoelectric element increases, the acoustic impedance gradually decreases, which is conducive to better matching with the acoustic impedance of air, increasing ultrasonic transmittance, and improving ultrasonic energy transmission efficiency.
[0052] However, as the porosity of ceramics increases, the strength of ceramics decreases, and the piezoelectric performance decreases. In this experiment, porous ceramics with a porosity of 70% are selected as piezoelectric elements (d 33 : 327pC / N, acoustic impedance: 5.95MRayl).
[0053] Example 6
[0054] A porous lead-free piezoelectric ceramic component, wherein the hole shape is spherical, and the rest is the same as Example 1.
[0055] Example 7
[0056] The air-coupled porous ultrasonic transducer comprising the porous lead-free piezoelectric ceramic element prepared in Example 5 is prepared as follows:
[0057] Step 3: Preparation of air-coupled porous ultrasonic transducer
[0058] Preparation of matching layer: E51 epoxy resin, T31 curing agent and hollow glass microspheres were mixed in a mass ratio of 5:1:6. Cured at 80°C for 8 hours, and the cured matching layer was polished to 2 mm. The matching layer was bonded to the porous piezoelectric ceramic by connecting the porous piezoelectric element with wires, and an air back was selected to obtain an air-coupled porous transducer.
[0059] like Figure 6As shown, the sensitivity of the air-coupled transducer tested at 10cm is -27dB, which is a significant improvement compared to the -30 to -40dB on the market. It can better detect small signals generated by partial defects in materials and analyze deep defects in materials.
[0060] Comparative Example 1
[0061] Porosity 40% piezoelectric ceramic support d 33 372pC / N, g 33 The acoustic impedance is 13 MRayl and the transducer is prepared as follows: Figure 7 As shown:
[0062] The test results show that its sensitivity is -46dB, which is poorer than the porous piezoelectric ceramic with a porosity of 70%.
[0063] Comparative Example 2
[0064] The piezoelectric ceramic support with a porosity of 80% was damaged due to its low strength during the printing, sintering and thermal polarization processes due to its high porosity, making its structure incomplete and difficult to use for the preparation of air-coupled porous ultrasonic transducers.
[0065] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an air-coupled porous lead-free ultrasonic transducer, characterized in that: The air-coupled porous lead-free ultrasonic transducer includes a porous lead-free piezoelectric ceramic element; The porous lead-free piezoelectric ceramic components are made by photocuring 3D printing of lead-free ceramic powder. The pores in the porous lead-free piezoelectric ceramic components are evenly distributed, the porosity is 55%-75%, and the pore structure is Gyroid; The epoxy resin, the curing agent and the hollow glass microspheres are mixed in a mass ratio of 5:1:5-6, and cured at 80° C. for 8-12 hours to obtain a matching layer, and the cured matching layer is polished to 2 mm; Connecting the porous lead-free piezoelectric element with a wire to bond the matching layer to the porous piezoelectric ceramic to obtain an air-coupled porous transducer; The preparation of porous lead-free piezoelectric ceramic components includes: S1. Preparation of lead-free ceramic powder According to the chemical formula 0.51Ba(Zr 0.2 Ti 0.8 )O3-0.49(Ba 0.7 Ca 0.3 )TiO3, BaTiO3, TiO2, CaCO3, ZrO2 powders are placed in a ball mill, and anhydrous ethanol is poured into the powder; the ball mill is placed in a ball mill, and ball milled at a speed of 260r / min for 10 to 14h; the powder is obtained after drying; the powder is placed in a crucible and pre-fired in a muffle furnace, and during pre-fired, the temperature is raised to 1220 to 1250°C at a heating rate of 4 to 5°C / min and kept warm for 3 to 5h; the pre-fired ceramic powder is placed in a ball mill and anhydrous ethanol is added, and ball milled at a speed of 260r / min for 20 to 30h; the ball mill slurry is dried for 12 to 14h to obtain ceramic powder, and the ceramic powder is passed through a 60 to 100 mesh sieve to obtain a fine and uniform ceramic powder required for 3D printing; S2.3D printing porous lead-free piezoelectric ceramic components The ceramic powder obtained by S1 was made into printing slurry, which was poured into the DLP printer. The required void structure and void ratio were designed using the Matlab plug-in. 2 Print layer by layer at a power of 15s; Debind the printed parts, use a tube furnace for vacuum debinding, heat up to 200℃ at 0.2℃ / min, keep warm for 2h, heat up to 400℃ at 0.3℃ / min, keep warm for 3h; heat the debinded parts in a muffle furnace at 5℃ / min to 1500℃ and keep warm for 4h; In step S2, the ceramic powder obtained in S1 is made into a printing slurry, which specifically includes the following steps: The ceramic powder prepared by S1 is weighed and poured into a ball mill, and a dispersant and a surfactant are added in an amount of 1% by weight of the ceramic powder, anhydrous ethanol and zirconium oxide balls are added, and the mixture is ground at a speed of 300 rpm for 12 hours. After ball milling, it is placed in an oven for 10 hours to fully remove the anhydrous ethanol, and ground with a mortar, and passed through a 200-mesh fine sieve to finally obtain a ceramic fine powder with uniform particle size distribution and surface modification; the modified ceramic fine powder and a Triton X-100 dispersant in an amount of 0.5%-2% by weight of the piezoelectric ceramic powder are weighed, and then an acrylate monomer and a TPO photoinitiator in an amount of 1%-3% by weight of the monomer are weighed, and finally a non-silicon defoamer accounting for 0.5% to 0.6% of the total weight of the piezoelectric ceramic slurry is weighed, and the mixture is mixed by ultrasonic vibration for 30 to 40 minutes; and the mixture is placed in a ball mill, and ball milled at a speed of 250 rpm for 3 to 4 hours. The obtained slurry is then subjected to vacuum degassing treatment to finally obtain a piezoelectric ceramic printing slurry.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the lead-free ceramic powder is 0.51Ba(Zr 0.2 Ti 0.8 )O3-0.49(Ba 0.7 Ca 0.3 )TiO3.
3. The preparation method according to claim 1, characterized in that: The 3D printing also includes: using a Matlab plug-in to design the pore size, pore shape and porosity.
4. The preparation method according to claim 3, characterized in that: The shape of the hole includes any one of a spherical shape and a diamond shape.
5. The preparation method according to claim 1, characterized in that: The acrylic monomer includes any one of HEA, HDDA and TMPTA.
Citation Information
Patent Citations
Lead-free calcium barium zirconate titanate piezoelectric ceramics and preparation method thereof
CN101935212A
Active matching thickness mould pressing electropneumatic coupling ultrasonic transducer
CN106311584A
Ultrasonic response 4D printing porous ceramic part and preparation method thereof
CN113121256A
Preparation method of barium calcium zirconate titanate transparent ceramic
CN114804865A